NURSING CARE USING HANDHELD FANS (BASED ON ROY'S ADAPTATION MODEL) FOR PATIENTS WITH BRONCHOPNEUMONIA AND DYSPNEA - KK, Indra Frana Jaya; Zulfikri, Ahmad; Pratiwi, Afrida; Ningsih, Deasy Kurnia; Cahya, Febriani; Ayunani, Sabrina; Akbar, M Agung (LPPM STIKES Al-Ma'arif Baturaja, 2026)
Bronchopneumonia remains a common respiratory condition that frequently leads to impaired breathing patterns in pediatric patients. Dyspnea that is not properly managed may lead to hypoxia and increased respiratory workload. Simple, safe, and evidence-based non-pharmacological interventions are needed to alleviate dyspnea symptoms. One such intervention is handheld fan therapy, which works by stimulating trigeminal mechanoreceptors to improve breathing comfort and support physiological adaptation. This study aimed to implement and evaluate the effectiveness of handheld fan therapy based on the Roy Adaptation Model in managing impaired breathing patterns among patients with bronchopneumonia. This study employed a descriptive case study design. The subjects consisted of three pediatric patients diagnosed with bronchopneumonia who met the inclusion criteria. Data were collected through nursing assessment, clinical observation, physical examination, and medical record documentation. The handheld fan therapy intervention was administered twice daily for three consecutive days, with each session lasting 5–10 minutes. Nursing care implementation followed the Indonesian Nursing Diagnosis Standards (SDKI), Nursing Outcome Standards (SLKI), and Nursing Intervention Standards (SIKI). Data were analyzed descriptively to evaluate adaptive response changes in patients. The findings indicated that all patients presented with primary complaints of dyspnea and cough with a nursing diagnosis of impaired breathing pattern. Following three days of intervention, improvements in respiratory status were observed, including decreased respiratory rate, reduced dyspnea levels, decreased cough frequency, improved oxygen saturation, and increased patient comfort. Handheld fan therapy based on the Roy Adaptation Model is an effective non-pharmacological nursing intervention for reducing dyspnea and improving breathing patterns in patients with bronchopneumonia. This intervention has the potential to be integrated into evidence-based nursing practice for respiratory care management.